Ideal : the novel and the play - Rand, Ayn (New York : New American Library, 2015)
"Originally conceived as a novel but then transformed into a play by Ayn Rand, Ideal is the story of beautiful but tormented actress Kay Gonda. Accused of murder, she is on the run, and she turns for help to six fans who have written letters to her, each telling her that she represents their ideal a respectable family man, a far-left activist, a cynical artist, an evangelist, a playboy, and a lost soul. Each reacts to her plight in his own way, their reactions a glimpse into their secret selves and their true values. In the end, their responses to her pleas give Kay the answers she has been seeking. Ideal was written in 1934 as a novel, but Ayn Rand thought the theme of the piece would be better realized as a play and put the novel aside. Now both versions of Ideal are available for the first time ever to the millions of Ayn Rand fans around the world, giving them a unique opportunity to explore the creative process of Rand as she wrote first a book, then a play, and the differences between the two"--
"Includes the never-before-published novel"--Cover.
AAL
Keywords: Ideals (Aesthetics) -- Fiction; Fugitives from justice -- Fiction; Letter writing -- Fiction; FICTION / Political; FICTION / Psychological; DRAMA / American; Political fiction